Pyramiding of multiple resistant genes of blast and bacterial blight diseases in the background of rice (Oryza sativa) mega variety BRRI dhan29 - Mohammad Abdul Latif; Sheikh Arafat Islam Nihad; Rakibul Hasan; Lutfur Rahman; Touhidur Rahman Anik; Amal Chandra Manidas; Mamunur Rashid; Mohammad Ashik Iqbal Khan; Rejwan Bhuiyan (Current Plant Biology)
Blast and bacterial blight (BB) are the two major rice diseases in the world including Bangladesh. In this study, BB resistance genes (Xa21 and xa13) and blast resistance (Pi9 and Pb1) genes were pyramided into a mega variety, BRRI dhan29 through marker-assisted backcross breeding. IRBB58 was used as a BB-resistant donor and Pi9-US2, and Pb1-US2 were used as blast-resistant donors. Backcross was done between BRRI dhan29 and donor parents to develop BC3F1 population and then selfing was done to develop BC3F6 population. BC3F2 population was genotyped and phenotyped for segregation analysis and BC3F6 was evaluated for genotyping, phenotyping and morphological traits and yields. Chi-square analysis of BC3F2 data revealed that blast and BB resistance followed the single gene mendelian fashion (1:2:1 and 3:1). Two to four gene combinations were found in the advanced lines of the BC3F6 population. The yield of the advanced lines ranged from 6.42 (t ha−1) to 9.5 (t ha−1) and they showed resistant against blast and BB with mean disease scores ranging from 0.67 to 2.33 and 0.33–2.33, respectively. Finally, eight lines having four genes (xa13, Xa21, Pi9 and Pb1) were selected for multilocational (five locations) trials for yield performance and disease reaction. Mean yield data of eight advanced lines of all locations were varied from 6.48±0.15–8.38±0.11 t ha−1 and all the lines showed resistant reactions against blast (score 0.53–1) and BB (score 0.6–0.87) disease. The highest yield was found in BR (Path) 13800-BC3–224–12 (G28, 8.38±0.11 t ha−1) followed by BR (Path) 13800-BC3–134–252 (G26, 8.28±0.08 t ha−1) and BR (Path) 13800-BC3–136–115 (G12, 8.24±0.07 t ha−1). Pyramided advanced lines of this study could be released as BB and blast-resistant varieties or could be utilized as donor parents in resistant breeding.